2016
DOI: 10.1002/dc.23473
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Carcinoma Arising in a Mucinous Cystic Neoplasm Masquerading as Pancreatic Pseudocyst

Abstract: Mucinous cystic neoplasms (MCN) of the pancreas can vary from benign to premalignant and malignant. Preoperative diagnosis is essential to offer the patient appropriate treatment. Occasionally these cases may harbor anaplastic carcinoma while clinically masquerade as a pseudocyst. Here in, we report an unusual case of a 37-year old female presented with recurrent abdominal pain that was suspected clinically and by imaging studies to have a pseudocyst. EUS-FNA with internal drainage of the cyst was performed. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…6 ACP occurs most commonly in the head of the pancreas, 6,18 but it has been also described in the pancreatic body. 6,18,19 With a pooled sensitivity of 85% and 89% and pooled specificity of 98% and 99% in diagnosing pancreatic malignancies according to two meta-analyses studies, 20,21 EUS-FNA has been established as the gold standard initial approach for the assessment of pancreatic masses. One case series of ACP reported that four out of five patients (80%) were diagnosed with ACP on EUS-FNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 ACP occurs most commonly in the head of the pancreas, 6,18 but it has been also described in the pancreatic body. 6,18,19 With a pooled sensitivity of 85% and 89% and pooled specificity of 98% and 99% in diagnosing pancreatic malignancies according to two meta-analyses studies, 20,21 EUS-FNA has been established as the gold standard initial approach for the assessment of pancreatic masses. One case series of ACP reported that four out of five patients (80%) were diagnosed with ACP on EUS-FNA.…”
Section: Discussionmentioning
confidence: 99%
“…Reported EUS features of ACP include a hypoechoic tumor, with solid or mixed solid and cystic components and poorly defined borders; however, it can also present as a well‐defined homogeneous mass in some cases . ACP occurs most commonly in the head of the pancreas, but it has been also described in the pancreatic body …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a literature search with the terms “Anaplastic carcinoma pancreas” and “EUS-FNA”, using PubMed database for the period from 2006 to September 2016. We found seven reports of 19 cases of ACP during that period diagnosed by EUS-FNA (including our patient; Table 1 ) [ 5 11 ]. In most of the cases, the tumors were shown as hypoechoic and heterogeneous by EUS.…”
Section: Discussionmentioning
confidence: 99%